Android-Based Carriage Calculation Mobile Application Design using the Android Studio Ide (Integrated Development Environment) - Aris Budi Sulistyo; Riz Rifai O. Sause; I Nyoman Aris Pramanatha; Ni Wayan Widi Ayu Ariani; Bambang Wijonarko (Pusat Penelitian dan Pengabdian Masyarakat Poltrada Bali, 2022)
The growth of vehicles in Indonesia can lead to an increased risk of traffic accidents due to road user traffic violations, one of which is the Over Dimension Overloading (ODOL) vehicle violation. The unavailability of an application to calculate the specific payload capacity for Motor Vehicle Examiners to automatically test the calculation of the load capacity of a motorized vehicle, trailer and attached carriage is an important problem. This application is designed using the Android Studio IDE and Java programming with PHP as an intermediary xml and MySQL database. The analytical method used to formulate an application program design and system design is carried out to facilitate users. From the results of testing this application is said to be accurate and fast in carrying out the process of calculating the carrying capacity. The advantages of this application can provide consideration of whether or not a vehicle is able to withstand the strength of the carrying capacity in accordance with the carrying capacity of the vehicle and provide the results of adjusting the carrying capacity according to standards so as to reduce violations of Over Dimension Overloading (ODOL) vehicles on the highway.